2019
DOI: 10.1596/31465
|View full text |Cite
|
Sign up to set email alerts
|

Student Learning Outcomes in Tanzania’s Primary Schools

Abstract: This policy note is an attempt to systematically analyze and document emerging trends in the evolution of students' learning outcomes in Tanzania's primary schools. The note is based on two rounds of the Service Delivery Indicators Survey in Tanzania, 2014 and 2016, and provides guidance to the Government on: (1) regional, district and school-level variations in gains in pupil achievement scores; (2) student, teacher and school level factors associated with learning outcomes; and (3) key observable factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Other content areas less frequently mentioned were money, square and square roots, percentages, coordinate geometry and patterns. On the other hand findings by Asim et.al (2019) indicated that in the past, Tanzania has struggled to ensure primary school students are equipped with the basic skills of writing, reading and numeracy necessary for post-primary education. While the lack of knowledge in some mathematics contents by primary school students can be associated with the student's own abilities and learning environment, the gap may also reflect the extent of the teacher's capacity in the respective contents and in teaching methodology.…”
Section: Lack Of Knowledge and Understanding Of The Subject Mattermentioning
confidence: 99%
“…Other content areas less frequently mentioned were money, square and square roots, percentages, coordinate geometry and patterns. On the other hand findings by Asim et.al (2019) indicated that in the past, Tanzania has struggled to ensure primary school students are equipped with the basic skills of writing, reading and numeracy necessary for post-primary education. While the lack of knowledge in some mathematics contents by primary school students can be associated with the student's own abilities and learning environment, the gap may also reflect the extent of the teacher's capacity in the respective contents and in teaching methodology.…”
Section: Lack Of Knowledge and Understanding Of The Subject Mattermentioning
confidence: 99%
“…While exploring the causes of low performance of learners, researchers [11,12,13]. posit that within factors that fall into the purview of education, the effectiveness of the teacher in the classroom is the most important factor that determines learners learning.…”
Section: Antecedents Of Learning Crisismentioning
confidence: 99%
“…This plan abolished primary education school fees, increased the primary education budget and improved the quality of education by emphasizing teacher training. During this time, primary school enrollment doubled and student learning outcomes began to gradually improve (Asim et al , 2019; Oketch and Rolleston, 2007; Pesha, 2016). Although education in the country is progressing, serious deficiencies remain.…”
Section: Introductionmentioning
confidence: 99%
“…Although education in the country is progressing, serious deficiencies remain. Increased student attendance has created a shortage of supplies, such as desks and books, and many schools lack the proper infrastructure and staff to guarantee student safety (Asim et al , 2019; Lewin, 2009; Sifuna, 2007). Moreover, schools continue to lack qualified teachers and experience challenges in maintaining education quality, which adversely harm both rural and female students (Lewin, 2009; Oketch and Rolleston, 2007; Sifuna, 2007).…”
Section: Introductionmentioning
confidence: 99%